Setback distance and management for wetlands in plantation forests–a review of policy and practice in Australia and New Zealand - Myers, B.R.; Jones, Eriita; O’Hehir, J.; Lawson, J. (2022)
The management of wetlands within plantation forests is important for compliance with forest and timber certification schemes and legal requirements. This review considers how setback vegetation and management has been prescribed in policy, codes and guidelines in Australia and New Zealand, focusing on setback and buffer distances, why they are prescribed, and the evidence provided on their benefit. Our findings indicate that, although prescriptive guidance is generally provided for the establishment of setbacks and buffers, there is a lack of guidance on, for example, what vegetation should be in the setback or buffer zone and how it should be managed. There is also a lack of evidence in codes of practice, guidelines and policies to support the specified prescriptive distances. Requirements and recommendations should be evidence-based and assessed for effectiveness; where this knowledge is lacking, further studies should be undertaken to provide an evidence base.